Entwicklung und Charakterisierung von Siliziumnitrid-/Siliziumkarbidkompositen für den Einsatz in tribologisch hochbeanspruchten Gleitsystemen - Zielonka, Paul S. (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2023)
In this work, silicon nitride/silicon carbide composites are manufactured and characterized for tribologically highly stressed applications. The characterization of the composite materials shows the influence of the silicon carbide content on the resulting microstructure and the mechanical properties. The friction properties of the composite materials were characterized in tribological experiments. The composites show very good friction and wear behavior.